2023
DOI: 10.1109/access.2023.3248287
|View full text |Cite
|
Sign up to set email alerts
|

The Key Criteria for Predicting Unusual Behavior in the Elderly With Deep Learning Models Under 5G Technology

Abstract: Deep learning algorithms and technology based on 5G networks may be able to help identify unusual behavior in elderly people. Because 5G networks have a lower latency and a greater bandwidth, it is possible to use more complex algorithms and larger data sets for training and detection in a real-time. On top of that, real-time analysis of the data gathered through in-home monitoring of the elderly can become much simpler to carry out with the help of 5G's potential to simplify the process. However, the system n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…From the literature survey, the identified that the drawbacks of the Existing System are limited accuracy, dependency on wearable devices, a lack of continuous monitoring, environmental limitations, the inability to distinguish falls from other activities, and a lack of real-time assistance [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the literature survey, the identified that the drawbacks of the Existing System are limited accuracy, dependency on wearable devices, a lack of continuous monitoring, environmental limitations, the inability to distinguish falls from other activities, and a lack of real-time assistance [14].…”
Section: Literature Reviewmentioning
confidence: 99%